HUBUNGAN KECEMASAN DENGAN EFIKASI DIRI PADA MAHASISWA BARU FAKULTAS KEPERAWATAN UNIVERSITAS RIAU - Shelpi Pebriani; Darwin Karim; Gamya Tri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Introduction: New students in their tertiary institutions have to adapt to their new environmental situation as students both academically and non-academically, this is a trigger for anxiety and depression in early grade students. One of the efforts to overcome anxiety is how individual perceptions and assessments of the situation at hand, namely the aspect of confidence in self-efficacy called self-efficacy. The purpose of this study was to determine the relationship between anxiety and self-efficacy in new students of the Faculty of Nursing, University of Riau. This study used a descriptive correlation research design through a cross sectional approach. The number of samples in this study were 107 people who were taken using the simple random sampling technique. The measuring instrument used was a questionnaire that had previously been tested for validity and reliability. The analysis used is univariate and bivariate analysis with an alternative test, namely Fisher Exact. The results showed that there was a significant relationship between anxiety (p value 0.000 <0.05) and self-efficacy. Based on the results of this study, it is expected to be a source of information in the development of knowledge about the relationship between anxiety and self-efficacy in new students. Keywords: Anxiety, Self-Efficacy, Student